The Factors Influencing Consumer Behaviour in the Purchase of Green Products in Windhoek, Khomas Region of Namibia - Benedict Sewe, Odhiambo (INTI International University, 2024)
It is a global concern that environmental sustainability is in danger. Climate conditions in most parts of the world cannot sustain agriculture and livestock, while water and energy shortages remains a huge challenge. While enjoying products and services offered in the market, consumers should protect their environment and maintain a healthy life style by purchasing green products which are environmental friendly. Prospective green consumer’s expression of interest in green products is not converted into actual purchase. The objective of this study is to examine the factors that influence consumer behavior in the purchase of green products. The study adopted mixed methods and a sample of 120 respondents was considered. SPSS was used for analysis. Qualitative data was analyzed using thematic analysis. Statistical significant association was found between the purchases of green products with the eight main predictors which are; Environmental attitudes, perceived effectiveness of environmental problems, perceived environmental responsibility, green products labelling, green product features, green product certification, environmental benefits of green products, governments concern about the environment. The study found a negative association between purchase of green products and consumers knowledge about environmental benefits. By gathering this information, marketers would be able to understand the factors which influence consumers in the purchase of green products. They would also be able to formulate various strategies to effectively attract more green consumers to purchase green products as part solution for environmental protection. The legislators, national policy makers and environmental activists could utilize this information to promote a positive green consumerism.